High-volume hospitals do not perform better than low-volume hospitals in septic and aseptic revision total hip arthroplasty: an analysis of re-revision risk and mortality based on the Dutch Arthroplasty Register - Marije C Vink; Rinne M Peters; Bart van Dooren; Amarens Deen; Liza N van Steenbergen; B Wim Schreurs; Wierd P Zijlstra (Acta Orthopaedica)
Background and purpose: Revision total hip arthroplasty (rTHA) is a complex procedure that may benefit from centralization. We examined the association between annual hospital volume of rTHA and re-revision risk and mortality. Methods: We included all rTHAs between 2007 and 2022 in general hospitals, registered in the Dutch Arthroplasty Register (LROI; n = 12,515). Hospitals were categorized into low (< 25 rTHA/year) or high volume (≥ 25 rTHA/year). Competing-risk analyses and Cox proportional hazard regression analyses were performed to assess implant re-revision and Kaplan–Meier survival analysis for mortality. Results were stratified into septic (permanent Girdlestone, 1-stage, and 2-stage revisions) and aseptic first revisions. Results: 1-stage septic revisions showed a higher risk of re-revision in high-volume hospitals (hazard ratio [HR] 1.6, 95% confidence interval [CI] 1.1–2.4). We found no difference in re-revision risk after DAIR (HR 1.1, CI 0.9–1.3). 2-stage septic revisions were more often performed in high-volume hospitals (5% vs 2%). There was no statistical difference in re-revision rates between hospitals after revision for aseptic loosening (HR 1.1, CI 0.9–1.4), dislocation (HR 1.1, CI 0.9–1.4), and periprosthetic fractures (HR 1.1, CI 0.8–1.5). Mortality showed no differences between groups, neither for septic nor aseptic revisions. Conclusion: There was no difference between high-volume hospitals and low-volume hospitals regarding risk for re-revision after aseptic loosening, dislocation and periprosthetic fracture, and septic DAIR and mortality. In high-volume hospitals, 1-stage septic revisions was associated with a significantly higher re-revision risk. 2-stage revisions are more frequent in high-volume hospitals, indicating more complex pathology.